The Impact of HLA-G 3′UTR Polymorphisms in Breast Cancer in a Tunisian Population. (4th July 2019) - Ouni, Nesrine; Chaaben, Arij Ben; Kablouti, Ghalia; Ayari, Fayza; Douik, Hayet; Abaza, Hajer; Gara, Sonia; Elgaaied-Benammar, Amel; Guemira, Fethi; Tamouza, Ryad
ABSTRACT: Human leukocyte antigens G and E (HLA-G and HLA-E) are nonclassical major histocompatibility complex (MHC) class I molecules. These molecules play an important role in immune surveillance by inhibiting natural killer and cytotoxic T cells responsible for immune escape. The expression of HLA-G and HLA-E has been associated with several diseases including tumor. The main objective of the study is to evaluate the impact of three HLA-G 3ʹUTR potential polymorphisms: +3187 A > G (rs9380142), +3142 G > C (rs1063320), +2960 14-base pair (bp) Insertion/Deletion (Ins/Del) (rs66554220), and the HLA-E*01:01/01:03 A > G (rs1264457) polymorphism in Tunisian breast cancer population. A total of 355 patients and 381 controls were genotyping for HLA-G and HLA-E polymorphisms using a Taq Man assay. +3142 C allele and +3142 C/C genotype were significantly associated with increased risk of breast cancer (p = 0.00002; OR = 1.58; 95% CI = 27–1.97) (49% versus 35%; p = 0.0001; OR = 1.79; 95% CI = 1.32–2.44). In addition, Del allele and the homozygous state for Del/Del genotype confer a risk for breast cancer (52% versus 45%, p = 0.006; OR = 1.33, 95% CI = 1.08–1.64) (28% versus 22%, p = 0.039; OR = 1.43, 95% CI = 0.90–2.25). However, no statistical significant differences were reported for HLA-G + 3187 A > G and HLA-E variations and breast cancer in a Tunisian population. The found results indicate that HLA-G may play an important role in the breast cancer.